Antimicrobial Stewardship: A Cross-Sectional Survey Assessing the Perceptions and Practices of Community Pharmacists in Ethiopia - Erku, Daniel Asfaw (Interdisciplinary Perspectives on Infectious Diseases, 2016)
Background. Community pharmacists are key healthcare professionals for antimicrobial stewardship programs owing to their role in dispensing of antimicrobials. The aim of the present study was to assess the perception and practices of community pharmacists towards antimicrobial stewardship (AMS) in Ethiopia. Methods. A cross-sectional survey was conducted by selecting pharmacy sites through stratified simple random sampling technique. Descriptive and inferential statistics were used to analyze the data. Results. Majority of respondents strongly agreed or agreed that AMS program is vital for the improvement of patient care. Almost all of respondents agreed that pharmacists can play a prominent role in AMS and infection prevention (93.2%, median = 5; IQR = 2–5). However, only 26.5% of respondents strongly agreed or agreed that AMS should be practiced at community pharmacy level (median = 4, IQR = 1–3) and more than half of community pharmacists (59.9%) often/always dispense antimicrobial without a prescription. Conclusion. The present study revealed positive perceptions and practices of community pharmacists towards antimicrobial stewardship. Yet, some weak areas like integration of AMS program in community pharmacies, the significance of interprofessional involvement, and dispensing of antimicrobials without a valid prescription still need improvement.